The Determinants Of Women And Its Impact On Poverty Alleviation : A Case Of Kwara State, Nigeria : A Pilot Study - Abdussalam, Onagun Isiaka; Fuadah Johari; Mohammad Haji Alias (Leena and Luna International (Pvt) Limited, 2024)
Volume :2 No: 4 (page: 342-347)